2009
DOI: 10.1016/j.gaitpost.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of healthy adults walking on a laterally oscillating treadmill

Abstract: Abstract:We mounted a treadmill on top of a six degree-of-freedom motion base platform to investigate locomotor responses produced by healthy adults introduced to a dynamic walking surface. The experiment examined self-selected strategies employed by participants when exposed to continuous, sinusoidal lateral motion of the support surface while walking. Torso translation and step width were used to classify responses used to stabilize gait in a novel, dynamic environment. Two response categories emerged. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…11). The increase in peak-to-peak COP position indicates an increase in step width, which is adjusted to compensate for lateral acceleration induced by external perturbations (e.g., Oddsson et al, 2004;Brady et al, 2009). The increase in lateral r.m.s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11). The increase in peak-to-peak COP position indicates an increase in step width, which is adjusted to compensate for lateral acceleration induced by external perturbations (e.g., Oddsson et al, 2004;Brady et al, 2009). The increase in lateral r.m.s.…”
Section: Discussionmentioning
confidence: 99%
“…Longer duration low frequency oscillations (0.2 to 0.5 Hz) of a treadmill on a six-axis motion platform (e.g., Brady et al, 2009;McAndrew et al, 2010) have been used to investigate postural responses to perturbations when walking but have not been representative of motions encountered in transport.…”
Section: Introductionmentioning
confidence: 99%
“…For example, postXight tests with returning astronauts have shown that repeat Xyers re-adapt to a 1-g environment more rapidly than Wrsttime Xyers (Bloomberg et al 1997;Reschke et al 1998;Peters et al 2011), which might indicate greater proWciency at re-weighting. Our ground-based work has elucidated a similar spectrum of performances in healthy adults walking in novel discordant conditions (Brady et al 2009) that might indicate inherent diVerences in weighting preferences. The ability to consistently predict which individuals are more likely to be challenged in discordant sensory conditions is the Wrst step toward preparing them with early, speciWed gait training.…”
Section: Introductionmentioning
confidence: 87%
“…Evidence suggests that approximately 30 % of healthy normals are "highly" visually dependent (Warren et al 1996;Keshner 2004;Streepey et al 2007;Brady et al 2009), so we anticipated that of the 10 experimental subjects we recruited for our training program, at least a few would be noticeably more visually dependent than the others. The training study aVorded an opportunity to retrospectively relate performance measures to visual dependence should subjects with high visual dependence end up in our subject pool.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, overground walking provides more familiar optic flow feedback and the option to freely modulate gait. Evidently, in some cases, the differences between these distinct locomotor modalities affect proprioceptive, vestibular, visual, and exteroceptive afferent information, and consequently influence locomotor control (Deshpande and Patla, 2005;Sorensen et al, 2002;Patla, 2003;Dickstein and Laufer, 2004;Brady et al, 2009;Dixon et al, 2000).…”
Section: Locomotor Modalities In Rehabilitation and Research 241 Ovmentioning
confidence: 99%